Bronchiolitis: Analysis of 10 consecutive epidemic seasons. Issue 12 (26th May 2016) - Cangiano, Giulia; Nenna, Raffaella; Frassanito, Antonella; Evangelisti, Melania; Nicolai, Ambra; Scagnolari, Carolina; Pierangeli, Alessandra; Antonelli, Guido; Papoff, Paola; Petrarca, Laura; Capocaccia, Paolo; Moretti, Corrado; et al.
Summary: Bronchiolitis is the leading cause of hospitalization in infants under 12 months. Our aims were to analyze epidemiological characteristics of infants with bronchiolitis over 10 consecutive seasons and to evaluate whether there are any clinical differences between infants hospitalized for bronchiolitis during epidemic peak months and infants in non‐peak months. We enrolled consecutive enrolled 723 previously healthy term infants hospitalized at the Paediatric Emergency Department, "Sapienza" University of Rome over the period 2004–2014. Fourteen respiratory viruses were detected from nasopharyngeal aspirates by molecular methods. Clinical and demographic data were extracted from clinical charts. Viruses were detected in 351 infants (48.5%): RSV in 234 (32.4%), RV in 44 (6.1%), hBoV in 11 (1.5%), hMPV in 12 (1.6%), co‐infections in 39 (5.4%), and other viruses in 11 (1.5%). Analyzing the 10 epidemic seasons, we found higher incidence for bronchiolitis every 4 years with a peak during the months December–January. Infants hospitalized during peak months had lower family history for asthma ( P = 0.003), more smoking mothers during pregnancy ( P = 0.036), were slightly higher breastfed (0.056), had lower number of blood eosinophils ( P = 0.015) and had a higher clinical severity score ( P = 0.017). RSV was detected mostly during peak months, while RV was equally distributed during the seasons. We found some variations in bronchiolitis incidence during epidemics, and discriminative characteristics in infants hospitalized for bronchiolitis during peak months and in non‐peak months, that might reflect two different populations of children.Pediatr Pulmonol. 2016;51:1330–1335. © 2016 Wiley Periodicals, Inc.